2017
DOI: 10.1016/j.antiviral.2017.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Screening of an FDA-approved compound library identifies levosimendan as a novel anti-HIV-1 agent that inhibits viral transcription

Abstract: Combination antiretroviral therapy (cART) has been proven to efficiently inhibit ongoing replication of human immunodeficiency virus type 1 (HIV-1), and significantly improve the health outcome in patients of acquired immune deficiency syndrome (AIDS). However, cART is unable to cure HIV-1/AIDS. Even in presence of cART there exists a residual viremia, contributed from the viral reservoirs of latently infected HIV-1 proviruses; this constitutes a major hurdle. Currently, there are multiple strategies aimed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…In this context, the Tat inhibitor didehydro-cortistatin A (dCA) has shown its ability to inhibit ex vivo residual viral replication under ART and to prolong the time to viral reactivation after treatment interruption (Kessing et al, 2017), but some in vitro resistance mutations to dCA were reported (Mousseau et al, 2019). Currently, several drugs are identified for their ability to be used as LPA (Latency Promoting Agents) to ensure a functional cure (Suzuki et al, 2013;Wan and Chen, 2014;Vranckx et al, 2016;Hayashi et al, 2017;Jean et al, 2017;Debyser et al, 2018). Undeniably several strategies must be exploited in order to reach a functional cure.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, the Tat inhibitor didehydro-cortistatin A (dCA) has shown its ability to inhibit ex vivo residual viral replication under ART and to prolong the time to viral reactivation after treatment interruption (Kessing et al, 2017), but some in vitro resistance mutations to dCA were reported (Mousseau et al, 2019). Currently, several drugs are identified for their ability to be used as LPA (Latency Promoting Agents) to ensure a functional cure (Suzuki et al, 2013;Wan and Chen, 2014;Vranckx et al, 2016;Hayashi et al, 2017;Jean et al, 2017;Debyser et al, 2018). Undeniably several strategies must be exploited in order to reach a functional cure.…”
Section: Resultsmentioning
confidence: 99%
“…The Planelles model of HIV-1 latency was used to generate latently infected CD4 + T cells with slight modifications (Bosque and Planelles, 2009 ; Hayashi et al, 2017 ; Huang et al, 2017 ). Briefly, naïve CD4 + T cells were isolated from two healthy PBMC donors and were stimulated with anti-CD3/CD28 antibodies that were precoated on a Nunc-Immuno Maxi Sorp plate (Thermo Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…These two compound libraries can provide suitable objects to be investigated for new inhibitors. [26][27][28][29][30][31][32][33] Thus, we focused on these two commercial compound libraries and performed high-throughput screening to seek new Elp2 inhibitors.…”
Section: Discussionmentioning
confidence: 99%